Youth Crime, Family Violence and Labor Market. The Configurations of Family Neglect Among Adolescents in Conflict With the Law in Mexico City - Gabriel Tenenbaum Ewig (Estudios Sociológicos, 2018)
This paper attempts to show the socio-structural conditions that lead families to become a social group that increases the risk of law infractions among adolescents. In particular, the research analyzes the influence of precarious work market conditions and domestic violence on the material and immaterial care that the family referents provide to the adolescents in conflict with the law. The research is conducted via a qualitative research design consisting on interviews to family referents (mothers, fathers, grandmothers) of the adolescents sanctioned by justice and interviews to judicial operators of the adolescent’s justice system in Mexico City.